Reframing indigenous biography
1 online resource (xviii, 315 pages)
Keywords: "This book explores the history, practice and possibilities of writing about the lives of First Nations' peoples in Australia as well as Aotearoa New Zealand, North America and the Pacific. This interdisciplinary collection recognises the limitations of Western biographical conventions for writing Indigenous long and short-form biographies. Through a series of diverse life stories of both historical and contemporary First Nations figures, investigates innovative ways to ameliorate the challenges we face in recovering the stories of Indigenous people and reimagining their lives in productive new ways. Many of the chapters in this collection are deeply reflective, aiming not just to relate the life story of an individual but also to reflect on the archival, intellectual and emotional journeys that biographers undertake in researching Indigenous biography. This volume will be of value to scholars and students interested in Indigenous Studies, biography, history, literature, creative writing, archaeology, and colonial and postcolonial studies"--